High potential for reducing folic acid‐preventable spina bifida and anencephaly, and related stillbirth and child mortality, in Ethiopia. Issue 19 (19th August 2019) - Dixon, Meredith; Kancherla, Vijaya; Magana, Tony; Mulugeta, Afework; Oakley, Godfrey P.
Abstract: Background: Recent surveillance studies in Ethiopia show an epidemic of spina bifida and anencephaly, two major neural tube birth defects that are severe and life‐threatening. Our objective was to estimate proportional reductions in current stillbirth and child mortality rates in Ethiopia through folic acid‐based interventions to prevent spina bifida and anencephaly. Methods: Using secondary data from multiple sources, we estimated percent reductions in stillbirth, neonatal, infant, and under‐five child mortality rates that would have occurred in Ethiopia in the year 2016 had all folic acid‐preventable spina bifida and anencephaly been prevented; and the contributions of these reductions toward Ethiopia's Year 2030 Every Newborn Action Plan (ENAP) goal on stillbirth, and sustainable development goal (SDG) on child mortality rates. The 2016 prevalence of spina bifida and anencephaly in Ethiopia was assumed as 13 per 1, 000 total births, with the prevention goal reaching 0.5 per 1, 000 total births. Results: Folic acid interventions in Ethiopia would have prevented about 41, 610 cases of folic acid‐preventable spina bifida and anencephaly‐affected pregnancies during the year 2016. We estimate that this prevention is associated with reduction of 31, 830 stillbirths and 7, 335 under‐five child deaths annually. The proportional contribution of this prevention toward achieving Ethiopia's ENAP goal is 54% for stillbirth, and toward SDG is 4.5% for neonatal‐ and 6.8% for under‐five mortality. Conclusions: Spina bifida and anencephaly contribute to substantial stillbirths and child death in Ethiopia. Large‐scale fortification of foods like wheat flour and salt can help achieve Ethiopia's ENAP and SDG targets addressing preventable stillbirth, neonatal, and under‐five mortality.